2003
DOI: 10.1080/00131910303250
|View full text |Cite
|
Sign up to set email alerts
|

Bookstart: A qualitative evaluation

Abstract: Bookstart, an early intervention strategy to develop the foundations of literacy in children's early years, was developed in Birmingham 10 years ago. Virtually all the research, conducted over that time, which made it a national and international project, was quantitative in nature. This research is contextualised and reviewed in the early sections of this paper. However, the importance of the data presented here is that they are qualitative and represent the views of professionals engaged in a Bookstart proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 8 publications
0
21
0
4
Order By: Relevance
“…Research has shown that reading to young children increases their future literacy achievement (Moore & Wade, 2003), increases vocabulary, knowledge of print (Reese & Cox, 1999), language acquisition, early reading performance, and school success (Snow, Burns, & Griffin, 1998). Although the benefits of reading aloud are extensive, reading aloud often limits a child's involvement in the reading process to more of a passive role.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that reading to young children increases their future literacy achievement (Moore & Wade, 2003), increases vocabulary, knowledge of print (Reese & Cox, 1999), language acquisition, early reading performance, and school success (Snow, Burns, & Griffin, 1998). Although the benefits of reading aloud are extensive, reading aloud often limits a child's involvement in the reading process to more of a passive role.…”
Section: Introductionmentioning
confidence: 99%
“…Such longer term assessments of interventions with young children are comparatively rare in the educational research literature, although we began this paper by referring to, perhaps, the best known longitudinal study in the area, that of Schweinhart et al (2005). For interventions comparable to that evaluated here, the example of Moore & Wade (2003) has been influential, although even in this case, the evidence stops when the children involved reached 7 years old. Research needs to be conceived over a longer time scale if a true costs-benefits analysis is to be achieved for projects such as Booktime.…”
Section: Resultsmentioning
confidence: 99%
“…O'Hare and Connolly (2010), for example, have reported strong evidence of a positive effect of Bookstart on parents' attitudes to reading and books and some evidence of an improvement in parental attitudes to their child reading. The longitudinal study reported by Wade and Moore (2000) and Moore and Wade (2003) has suggested that being involved in the Bookstart programme had led to an improvement of language and literacy performance upon school entry at the age of four. Tracking children's performance up to their Key Stage 1 assessment at age seven, Wade and Moore's research suggests that Bookstart children maintained this advantage throughout their first three years of primary education.…”
Section: Exploring a National Book-gifting Scheme: Parents' And Childmentioning
confidence: 99%
“…In particular, encouraging parents/carers to share books with their baby from birth has been identified as having positive educational, social and emotional outcomes (Hardman and Jones 1999;Evans, Shaw, and Bell 2000;Moore and Wade 2003). Evidence from a number of national and international studies has identified a positive connection between shared book reading and early literacy learning (Bus, van Ijzendoorn, and Pellergrini 1995;De Temple and Snow 2003;Karrass and Braungart-Rieker 2005).…”
Section: Literature Reviewmentioning
confidence: 93%